2018
DOI: 10.1016/j.canlet.2018.01.047
|View full text |Cite
|
Sign up to set email alerts
|

FBW7 loss promotes epithelial-to-mesenchymal transition in non-small cell lung cancer through the stabilization of Snail protein

Abstract: The E3 ubiquitin ligase F-box and WD repeat domain containing 7 (FBW7α) functions as a putative tumor suppressor in non-small cell lung cancer (NSCLC) due to its regulation of a set of oncogenic proteins associated with cell proliferation and mitosis. Increasing efforts have been focused on the understanding of FBW7 in determining cell cycle progression and apoptosis induction, however, the correlation between FBW7 and tumor metastasis is not fully understood. In this study, we reported a potential anti-metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…Snail is a liable protein and degraded by ubiquitin-proteasome system. Although several E3 ubiquitin ligases for Snail degradation have been identified (31)(32)(33), the DUBs for the stabilization of Snail remain less defined. In this study, we identified USP3 serves as a bona fide DUB mediating Snail stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Snail is a liable protein and degraded by ubiquitin-proteasome system. Although several E3 ubiquitin ligases for Snail degradation have been identified (31)(32)(33), the DUBs for the stabilization of Snail remain less defined. In this study, we identified USP3 serves as a bona fide DUB mediating Snail stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, Brg1 functions as a chromosome modifier, affecting several gene sets associated with cell migration and cell mobility 41 . During the peer-review of this paper, a report about FBW7 directly regulating the ubiquitination and proteolysis of Snail in NSCLC (non-small-cell lung cancer) cells 42 prompted us to further analyze which plays more critical role in the EMT regulation by FBW7. In Supplementary Figure 12b and c, we could observe the increased migration induced by Brg1 overexpression was significantly rescued by Snail knockdown, but not to the normal level (EV group), which means except Snail, other Brg1 targets including the reported E-cadherin that participate in regulating cell migration and tumor metastasis in the gastric cancer setting requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin suppresses initiation and epithelial-mesenchymal transition (EMT) in early-stage gastric carcinogenesis 16,17 . Previous studies indicated that loss of F-box and WD-repeat domaincontaining 7 (FBW7) induced EMT in cancers 18,19 . The Snai1 transcriptionally represses E-cadherin and promotes tumor proliferation and invasion 20,21 .…”
Section: Introductionmentioning
confidence: 99%